Human nature & education: An analysis between Western and Islamic psychologies - Abdul Razak, Mohd Abbas; Haneef, Sayed Sikandar Shah; Mustapha, Maziah (2018)
This presentation focuses on the different concepts of human nature and their impact on education. To carry out this task the researchers selected ideas on man provided by three mainstream psychology of the West and compared them with the Islamic psychology. After comparing ideas on man from the Western and Islamic psychological viewpoints, the researchers went on further to analyze the most likely type of person that can be produced by applying each concepts in education. The result has indicated that all the three Western schools did explain some aspects of human nature, but nothing was more comprehensible than what has been explained in Islamic psychology. The West can learn the philosophical ideas on the creation of a good man from the Islamic perspective. Likewise, Islamic psychology which is philosophical in nature, can adopt some aspects of the scientific methods in understanding man provided by Western psychology.